Authority of Samarinda City Governments in Giving License to Open State Land - Adelina Silvia Bilqis; Istislam Istislam; Diah Aju Wisnuwardhani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Thesis is entitled "Authority of Samarinda City Governments in Giving License to Open State Land" with 2 (two) main issues, namely: (1) What are the criteria for rejection and acceptance that must be used as guidelines by the Notary Honorary Council for requests for approval of the process? summons to notaries who are not classified as obstruction of justice? (2) What is the legal protection for a Notary whose criteria are not classified as obstruction of justice by the Notary Honorary Council? Besides, this research is a kind of normative research. The research approach used is the statutoryapproachand theconceptual approach. The results of this thesis research indicate that the legal certainty of the decision of the Notary Honorary Council regarding the granting of a Notary summons permit by law enforcers can be formed if law enforcers can fully understand the functions of the Notary Honorary Council. In addition, the Notary Honorary Council must be consistent in making decisions so that there is legal certainty for the Notary. The Central Notary Honorary Council must conduct an examination of the Notary so that the good name of the position is protected and fully guarantees whether the Notary has made a genuine mistake personally or from the parties in the deed. The case should be suspended by the Notary Honorary Council as a form of protection for the position of a Notary, unless the Notary will be examined in a criminal case that has nothing to do with the making of the Notary deed. So that the Notary Honorary Council is not involved with the Obstruction of Justice. In the case of giving testimony, a Notary cannot disclose the deed he made either in part or in whole to other parties, this is in accordance with Article 66 paragraph 1 of the UUJN because as a trustee, the Notary is obliged to keep everything that is notified to him secret in his position as a Notary, even though there are some that are not included in the deed, and have been considered to represent the Notary in a trial so that the deed made by or before the Notary is a piece of evidence that has perfect evidentiary power.